(untitled) (Marketing Journal, 2026)
Abstract The article examines the importance of non-tariff regulation of foreign trade as an effective tool for managing trade and political relations. It analyzes the need to consider the potential for imbalances in supply and demand within the country when establishing quantitative restrictions on export and import quotas, provided the economic conditions for their application exist. Recommendations for improving the use of quotas in customs regulation of foreign trade in our country are developed. Keywords: non-tariff measures, quota, export quotas, import quotas, quota volume, foreign trade.